PROCEDURES FOR MANAGEMENT AND WITHDRAWAL OF PARKING PAYMENTS WITH "CARCIS" AT THE EDGE OF THE PUBLIC ROAD (STUDY ON IMPLEMENTATION OF REGULATION OF THE REGENT OF BANJARNEGARA NUMBER 88 OF 2017 CONCERNING IMPLEMENTATION GUIDELINES FOR MANAGEMENT OF PARKING - Fevtianinda, Salmania; Hartariningsih, Ninik; Djatmiko, Agoes (Ganesha Law Review, 2021)
Public roadside parking has become main requirement and the demand grows quite rapidly in common activity. For the time being, the procedures for parking management and withdrawal of parking payments accompanied by â€œTicketâ€ have been regulated by Regional Government. The purpose of the study of study is to explore and provide information on related subjects regarding the procedures for parking payment withdrawals accompanied by â€œTicketâ€ in accordance with applicable regulations, namely Regent Regulation Number 88 of 2017 concerning Guidelines for Managing Parking Levies Management in Banjarnegara Regency, which are expected can be useful applied in parking procedures in Banjarnegara. Generally, the study is using the Normative Juridical method and descriptive analytical research specifications while the method or presenting data will be presented in the form of a breakdown based on qualifications then arranged systematically. In Conclusion: It can be concluded thah the Procedure for Parking Management and Withdrawal of Parking Payments Accompanied by the â€œTicketâ€ on the Side of Public Road is closely related to the Regional Government which is obliged to carry out guidance and supervision of Regents Regulations in the form of Public Roadside Parking. Furthermore, parking and ticket procedures related to parking taxes and parking levies on the side of public roads so that they are in accordance with Regent Regulation Number 88 of 2017.